Studi Literatur: Peranan Perkembangan Fintech pada Kekuatan dan Peluang di Bank Syariah Berdasarkan Perspektif Ekonomi Islam - Agung Budiman; Irvan Widi Santoso; Agus Eko Sujianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In today's increasingly advanced era, all human needs cannot be separated from technology. The development of technology in the financial sector, known as Financial Technology (Fintech), has made all entities, especially banking, including Islamic banks, use the role of fintech as an opportunity and strength in developing their business. The development and use of sharia banking technology has become a matter of debate because it is feared that it will not be in accordance with sharia economic views in its operations. The aim of this research is to find out the strengths and opportunities of the development of Financial Technology for Islamic banks based on an Islamic economic perspective. By using a qualitative approach in the form of literature study. Data collection in this research was by observation, reading and concluding existing data collected from various sources, journals, websites, articles. The results of this research show that the role of fintech development in the strengths and opportunities in Islamic banks has a positive impact regarding the strengths and opportunities that make Islamic banks able to compete with conventional banks in attracting customer attention. Apart from that, sharia banking continues to use Islamic teachings as a reference in carrying out all operational flows in sharia banking so that this does not deviate from the provisions of Islamic economics. There are several points in the main sources of Islamic law which make the existence of fintech in sharia banking permitted as long as it does not contain elements of elements that are forbidden in Islam.